Reformasi Administrasi Pelayanan Berbasis Online pada Dinas Penduduk dan Pencatatan Sipil Kota Padang - Satrio Hadi Sutanto; Fina Jantika Putri; Natasya Herlianti; Rona Jauza; Wulan Guritna; Syamsir Syamsir (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
Public service can be said as a mirror of the relationship between the government and its citizens. Public services are also a medium for channeling the government's attention to the demands and needs of its people, especially at the present time where we are entering the era of society 5.0 which is defined as a period of intense human competition because various sectors of life coexist with the use of communication technology. The implementation of E-government has also been widely implemented in several government agencies in Indonesia, including the Population and Civil Registration Office of the City of Padang, West Sumatra, with the use of an online-based service system to improve service quality and quality. This is in accordance with the statement by the Head of the Padang City Disdukcapil Edi Hasymi who said that "this online service follows up on an appeal from the Ministry of Home Affairs for Disdukcapil in each district/city to implement online adminduk services to make it easier for people to carry out adminduk services"